Martin Luther's Bible. Perspectives on a rich legacy. Pp. vii + 193 incl. 19 ills. Edited by W. Gordon Campbell. Cambridge: James Clarke and Co., 2024. £25 (paper). 978 0 227 17918 5 - Hequet, Suzanne (The journal of ecclesiastical history, 2025)
Martin Luther's Bible. Perspectives on a rich legacy. Pp. vii + 193 incl. 19 ills. Edited by W. Gordon Campbell. Cambridge: James Clarke and Co., 2024. £25 (paper). 978 0 227 17918 5 - Volume 76 Issue 3